What do local governments teach about in ethics training? Compliance versus integrity. (2nd October 2021) - Perlman, Bruce J.; Reddick, Christopher G.; Demir, Tansu; Ogilby, Suzanne M.
ABSTRACT: Ethics research has focused on issues such as codes of conduct and ethical values and less on ethics training. This paper examines evidence from a national survey of local governments on what approaches they take to ethics training through the topics they teach. Our analysis showed that they use both of the two common types of training approaches: "compliance-based, " focusing on enforceable rules, and "integrity-based, " which aims more at instilling values. The research showed that the compliance-based approach was most commonly used, and integrity-based topics were less heavily emphasized. It found that these training topics were most likely to be offered in the Midwest, and managers were given the same training as employees. Population size and form of government did not register much impact. The results support prior research that local governments more often take the "low road" in ethics training and do not teach values and public interest topics.